Outpatient pediatric care during the COVID-19 pandemic, Almaty, Kazakhstan 2021–2022 - Kozhekenova, Nailya; Santric-Milicevic, Milena; Nurgaliyeva, Zhansaya; Oshibayeva, Ainash; Jeremic, Danilo; Dinic, Milan; Kyrykbayeva, Saltanat; Zhagiparova, Zhanar; Smasheva, Arshat; Miller, Anastassiya; Tolekova, Shyryn; Glushkova, Natalya (Frontiers in Public Health, 2025)
Background/objectivesDuring the COVID-19 pandemic, primary health care systems worldwide adapted to manage cases in outpatient settings, including those involving children. The aim of this study was to investigate the epidemiological characteristics of 27,205 outpatient COVID-19 cases among children (0–17 years) in Almaty, Kazakhstan, from 1 January 2021 to 31 December 2022, compared with major epidemiological events and public health measures.MethodsA cross-sectional analysis was conducted to assess the likelihood of hospitalization regarding demographic characteristics, concomitant diseases, the severity of COVID-19 course, as well as the dynamic of cases.ResultsThe majority of children (99.3%) were asymptomatic or mild. Children in the younger age group (0–4) had a higher risk of severe course and hospitalization compared with adolescents aged 15–17 years. Sex and chronic diseases (diabetes mellitus, obesity and chronic obstructive pulmonary disease) did not demonstrate statistical significance. The longest spike in outpatient COVID-19 cases in children coincided with the circulation of Delta and Eta strains, the highest with Omicron.ConclusionAmong outpatient COVID-19 cases in children, the likelihood of severe forms and hospitalization is higher if the child is under 5 years of age.